2013
DOI: 10.1038/ncomms2822
|View full text |Cite
|
Sign up to set email alerts
|

FTO-mediated formation of N6-hydroxymethyladenosine and N6-formyladenosine in mammalian RNA

Abstract: N6-methyladenosine (m6A) is a prevalent internal modification in mRNA and non- coding RNA affecting various cellular pathways. Here we report the discovery of two additional modifications, N6-hydroxymethyladenosine (hm6A) and N6- formyladenosine (f6A), in mammalian mRNA. We show that FeII- and α-ketoglutarate (α-KG)-dependent fat mass and obesity associated (FTO) protein oxidizes m6A to generates hm6A as an intermediate modification and f6A as a further oxidized product. hm6A and f6A have half-life times of ~3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
433
3
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 399 publications
(450 citation statements)
references
References 35 publications
12
433
3
2
Order By: Relevance
“…This suggested that in addition to repair of DNA damaged by alkylating adducts, members of the AlkB family are likely to be key players in m 6 A demethylation in DNA. It remains to be seen whether the metastable intermediates, N 6 hmA and N 6 fA, have any independent role in DNA as proposed for modified RNA 100.…”
Section: How Are M6a Marks Reset?mentioning
confidence: 99%
“…This suggested that in addition to repair of DNA damaged by alkylating adducts, members of the AlkB family are likely to be key players in m 6 A demethylation in DNA. It remains to be seen whether the metastable intermediates, N 6 hmA and N 6 fA, have any independent role in DNA as proposed for modified RNA 100.…”
Section: How Are M6a Marks Reset?mentioning
confidence: 99%
“…Three methyltransferases, including methyltransferase-like 3 (METTL3), methyltransferase-like 14 (METTL14), and Wilms' tumor 1-associated protein (WTAP), act as m 6 A writers and catalyze RNA m 6 A at specific sites with the consensus sequence [(G/A)GAC, where the underlined adenosine is the methylation site] (11,12). Two demethylases, fat mass-and obesity-associated protein (FTO) and AlkB homolog 5 (ALKBH5), both of which act as m 6 A erasers, reverse this process (13)(14)(15)(16)(17). Most m 6 A sites are located near the transcription start sites, exonic regions flanking splicing sites, stop codons, and the 3= untranslated region (3= UTR) (1, rabbit anti-m 6 A antibody and control IgG, followed by conversion of the input RNAs and the RNA immunoprecipitation (RIP) products into cDNAs with reverse transcriptase (RT) (Fig.…”
mentioning
confidence: 99%
“…Unlike Ψ, m 6 A modiications are reversible, suggesting that the modiications are involved in regulatory switches. Methyltransferases (METTL3, METTL14, and WTAP), termed writers, catalyze the methylation of adenosine [21][22][23], whereas demethylases (FTO and ALKBH5), termed erasers, remove the methyl group [24,25]. The m 6 A marks are recognized by YTH domain proteins, termed readers, which regulate mRNA processing and metabolism [26,27].…”
Section: An Overview Of Post-transcriptional Modiications Of Rnamentioning
confidence: 99%